The Influences of Social Determinants of Health on Health-Related Quality of Life in People with Hypertension: A Cross-Sectional Study. - Udomsap, Rudeewan; Phligbua, Warunee; Wattanakikrileart, Doungrut; Sriprasong, Sarinrut; Vorasettakarnkij, Yongkasem (Pacific Rim International Journal of Nursing Research)
Hypertension is a signif icant public health issue worldwide, including in Thailand, and its prevalence is expected to continue increasing. The inability to control blood pressure among people with hypertension has a negative impact on both physical and mental aspects, causing negative consequences on health-related quality of life. This cross-sectional study explored factors influencing the health-related quality of life among people living with hypertension, guided by the Social Determinants of Health framework. Convenience sampling was used to obtain 183 people with essential hypertension, who attended follow-up visits at the general medicine clinic, outpatient department in a super-tertiary hospital in Central Thailand. Data were collected using several instruments, including a Personal Information Questionnaire and Health records, the short form of the Spanish Hypertension Quality of Life Questionnaire, the short version of the European Health Literacy Survey, the Neighborhood Scales, the Adherence to the Dietary Approaches to Stop Hypertension Diet Consumption Questionnaire, the Family Support Questionnaire, and the Barriers to Receiving Care Questionnaire. The data were analyzed using descriptive statistics and stepwise multiple regression analysis. The f indings indicated that all participants (100%) had a good health-related quality of life. Health literacy, neighborhood resources, and barriers to receiving care together contributed to 22.1% of the variance explained in health-related quality of life in people with hypertension. Barriers to receiving care had the highest predictive power, followed by neighborhood resources, and health literacy. Thus, nurses should promote health literacy by encouraging people to obtain information from accurate and reliable sources, recognize the importance of using adequate resources in their neighborhood for their illness, and identify obstacles to accessing treatment to promote a healthy quality of life in people with hypertension.